Acquired Skin Fragility Syndrome and Diabetes Mellitus Secondary to Hyperadrenocorticism in a Cat - da Silva, Ana Paula; Fighera, Rafael Almeida (Acta Scientiae Veterinariae, 2018)
Background: Acquired skin fragility syndrome is a rare disorder which affects adult to senior cats with no history of skin trauma. Acquired skin fragility syndrome and diabetes mellitus, unlike the dog, are highly associated to feline hyperadrenocorticism (HAC) and, often, undiagnosed, what may accentuate the skin lesions and cause management complications. This report aimed to describe a case of acquired skin fragility syndrome and diabetes mellitus secondary to spontaneous hyperadrenocorticism in a cat, focusing on the chronic dermatological signs and their management, as well as on the treatment of the primary disease. Case: An approximately 7 year-old male mixed breed feline was admitted to the University Veterinary Hospital of an Institution with a history of polyphagia, polyuria and polydipsia, and skin ulcers on the trunk and in the cervical region about 2 months after onset and difficult to heal. Laboratory examinations indicated leukocytosis with lymphopenia, decreased urine specific gravity, glycosuria and hyperglycemia. The fasting plasma glucose level, the dexamethasone suppression test and the bilateral adrenal gland enlargement, visualized by ultrasonography, revealed diabetes mellitus and spontaneous hyperadrenocorticism, respectively. Histological skin findings indicated feline acquired skin fragility syndrome. Skin wound treatment through cleaning, protection and antibiotic therapy, and administration of insulin and trilostane were performed. After 6 months of trilostane therapy, adrenocorticotropic hormone (ACTH) stimulation test was performed, which demonstrated normal cortisol values 4 h after administration, which allowed maintenance of the dosage. After 12 months of the diagnosis of skin fragility syndrome and diabetes mellitus secondary to HAC, the patient did not present new skin lesions, fasting glycemia was within the reference values without insulin therapy and maintained only the prescription of trilostane. Discussion: The pituitary-dependent hyperadrenocorticism was the cause of the skin fragility syndrome, and it could be confirmed by the dexamethasone suppression test and the ultrasonography, which demonstrated bilateral adrenal gland enlargement. Healing of the wounds caused by the acquired skin fragility syndrome as well as the absence of new lesions may occur if the primary cause is found and treated adequately. Signs of polyuria, polydipsia and polyphagia verified in the patient of this report are nonspecific and allow the suspicion of both diabetes mellitus and hyperadrenocorticism. The return of glycemia to basal levels and the interruption of insulin demonstrated that diabetes mellitus was transient and secondary to hyperadrenocorticism. Therefore, it is indicated in situations similar to the clinical condition described in the patient of this report, to perform tests for diabetes mellitus and HAC. Trilostane can reduce the clinical signs of hyperadrenocorticism, but sometimes maintenance of insulin therapy is needed. The use of the drug improved the skin lesions in the cat of the current report and also allowed for the interruption of insulin administration. Those skin lesions which are of spontaneous occurrence and persistent, with no previous history of trauma and that do not respond to treatment, may alert clinicians to investigate underlying causes of non-dermatological origin and guide owners through the likely slow skin lesions healing until diagnosis and adequate therapeutic response of the primary disease. Keywords: Cushing disease, feline, skin, trilostane, wound healing.